2007
DOI: 10.1021/la700474v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkyl Chain Length on Phosphate Self-Assembled Monolayers

Abstract: A series of alkyl phosphates with alkyl chain lengths ranging from C10 to C18 have been synthesized. Self-assembled monolayers (SAMs) of these molecules were prepared on titanium oxide surfaces by immersion of the substrates in alkyl phosphate solutions of 0.5 mM concentration in n-heptane/isopropanol. The SAMs were characterized by means of dynamic water contact angle (dCA) measurements, variable-angle spectroscopic ellipsometry (VASE), X-ray photoelectron spectroscopy (XPS), and polarization-modulated infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
209
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(243 citation statements)
references
References 40 publications
26
209
1
Order By: Relevance
“…Salts of these acids are used in cooling lubricants, e.g., waterbased cutting fluids. The low toxicity, ability to be chemisorbed on a metal surface, and some useful technological properties of acid esters of phosphoric acid continue to motivate researchers to look for effective corrosion inhibitors of various metals among these compounds and to study their protection mechanisms [5][6][7][8][9][10][11][12][13][14]. …”
mentioning
confidence: 99%
“…Salts of these acids are used in cooling lubricants, e.g., waterbased cutting fluids. The low toxicity, ability to be chemisorbed on a metal surface, and some useful technological properties of acid esters of phosphoric acid continue to motivate researchers to look for effective corrosion inhibitors of various metals among these compounds and to study their protection mechanisms [5][6][7][8][9][10][11][12][13][14]. …”
mentioning
confidence: 99%
“…Similar to nonpolymeric phosphonates, initial electrostatic interactions in solution are likely stabilized in the subsequent dehydration step by the formation of covalent aluminophosphonate bonds (Al-O-P), which are hydrolytically more stable than Si-O-P bonds (23,24,29). To date, phosphonate derivatizations of metal oxide surfaces have predominantly used monophosphonate-terminated alkanes to form SAMs (24,(30)(31)(32)(33) or complex polyethylenglycol-polyalkylphosphonate graft copolymers (34,35). To our knowledge, simple aliphatic polymers containing many phosphonate side groups have not previously been described for protein antifouling applications on metal oxide surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…23 In this study, nano titania P-25 (Evonik) was modified ex situ using OP. It has been already shown that using long alkyl chain phosphates led to increase the van der Waals interactions between the alkyl chains, all-trans conformation of the chains, increasing the packing density and therefore more surface OH groups are replaced with phosphate groups 24 which is not favorable to photocatalysis process ( Figure S2). OP with chemical formula (OH) 2 (O)PO(CH 2 ) 2 NH 2 was chosen to modify TiO 2 because of possessing short alkyl chain in order to assemble into a less dense structure.…”
Section: Surface Modifier Selectionmentioning
confidence: 99%